2020
DOI: 10.1007/s11920-020-01171-2
|View full text |Cite
|
Sign up to set email alerts
|

Inter-generational Effects of Technology: Why Millennial Physicians May Be Less at Risk for Burnout Than Baby Boomers

Abstract: Purpose of Review Younger generations of physicians are using technology more fluently than previous generations. This has significant implications for healthcare as these digital natives become a majority of the population's patients, clinicians, and healthcare leaders. Recent Findings Historically, healthcare has been slow to adopt new technology. Many physicians have attributed burnout symptoms to technology-related causes like the EMR. This is partly due to policies and practices led by those who were less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…Willingness to practice telemedicine might require more long-standing professional experience with patients and resultant self-confidence regarding diagnosis/treatment than use of other eHealth tools, such as electronic patient records, webinars, or monitoring apps. Besides, the acceptance and use of telemedicine as well as other digital tools might have increased significantly over the years among health care professionals of all age group and years of experience [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Willingness to practice telemedicine might require more long-standing professional experience with patients and resultant self-confidence regarding diagnosis/treatment than use of other eHealth tools, such as electronic patient records, webinars, or monitoring apps. Besides, the acceptance and use of telemedicine as well as other digital tools might have increased significantly over the years among health care professionals of all age group and years of experience [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…11,15 Older generations are just as willing to use telehealth during the pandemic, contrary to the resistance sometimes found among Baby Boomers. 26 Among those surveyed who use telehealth, most reported that they thought telehealth was effective in preventing suicides among American Indian communities in Montana during the COVID-19 pandemic. This survey also found that providers perceive suicide prevention services through tele-health as effective as face-to-face care (e.g., asking individuals direct and open questions and responding to those at risk for suicide), whereas providers viewed other tasks more ambivalently (e.g., transitions in care).…”
Section: Discussionmentioning
confidence: 99%
“…19,23,25 This telehealth resistance is higher among Baby Boomers (ages 56 to 73) who have been found to be less comfortable with digital technology, compared with Generation X (ages 40 to 55), Millennials (ages 24 to 39) and Generation Z providers (age 24 and under). 26 However, since the coronavirus pandemic, providers may be increasingly open to using telehealth as an option for delivery of the various aspects of suicide prevention service, including identification of warning signs, treatment for those at elevated risk for suicide, and transition support for patients navigating the health system. 15 This study sought to identify perceptions and attitudes of behavioral health and medical care providers on the impact of the coronavirus pandemic on suicide risks among American Indians in Montana, changes in suicide prevention care, adoption of telehealth, and the effectiveness and efficiency of telehealth for suicide prevention services.…”
mentioning
confidence: 99%
“…This finding may reflect generational changes in perceptions about work-life balance (and work-life integration), but there are also data to suggest that younger physicians will drive technological advancement and integration faster than previous generations to improve efficiency, allow more flexible working arrangements, and increase convenience for patients/physicians, making them perhaps more resilient to burnout than previous generations. 44 Ergonomic challenges facing vascular surgeons have recently garnered appropriate attention. Workload data recently reported by Davila et al 24 that more than 87% of surgeons operate 3 or more days per week and 4 or more hours per day with lead garments worn by almost one-half of these surgeons daily and more than 90% wearing lead at least once per week.…”
Section: Discussionmentioning
confidence: 99%